Proteomic Analysis of the Hydrogen and Carbon Monoxide Metabolism of Methanothermobacter marburgensis - Diender, Martijn; Pereira, Ricardo; Wessels, Hans J. C. T.; Stams, Alfons J. M.; Sousa, Diana Z. (Frontiers in Microbiology, 2016)
Hydrogenotrophic methanogenic archaea are efficient H2 utilizers, but only a few are known to be able to utilize CO. Methanothermobacter thermoautotrophicus is one of the hydrogenotrophic methanogens able to grow on CO, albeit about 100 times slower than on H2 + CO2. In this study we show that the hydrogenotrophic methanogen Methanothermobacter marburgensis, is able to perform methanogenic growth on H2/CO2/CO and on CO as a sole substrate. To gain further insight in its carboxydotrophic metabolism, the proteome of M. marburgensis, grown on H2/CO2 and H2/CO2/CO, was analysed. Cultures grown with H2/CO2/CO showed relative higher abundance of enzymes involved in the reductive acetyl-CoA pathway and proteins involved in redox metabolism. The data suggest that the strong reducing capacity of CO negatively affects hydrogenotrophic methanogenesis, making growth on CO as a sole substrate difficult for this type of methanogens. M. marburgensis appears to partly deal with this by upregulating co-factor regenerating reactions and activating additional pathways allowing for formation of other products, like acetate.